2017
DOI: 10.1038/s41598-017-02011-9
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional Penta-BP5 Sheets: High-stability, Strain-tunable Electronic Structure and Excellent Mechanical Properties

Abstract: Two-dimensional (2D) crystals exhibit unique and exceptional properties and show promise for various applications. In this work, we systematically studied the structures of a 2D boronphosphide (BP) monolayer with different stoichiometric ratios (BPx, x = 1, 2, 3, 4, 5, 6 and 7) and observed that each compound had a stable 2D structure with metallic or semiconducting electronic properties. Surprisingly, for the BP5 compounds, we discovered a rare penta-graphene-like 2D structure with a tetragonal lattice. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 41 publications
(49 reference statements)
2
30
2
Order By: Relevance
“…Usually with application of strain, the deep conduction band states near Fermi comparatively shifts to lower energy than the lowest conduction band states; this causes change in the nature of band gap between direct or indirect. 23 In some cases similar to the present case, the variation in the valence band is also authoritatively significant to decide the nature of the band gap. On the structural front, a large anisotropy of black phosphorous along with one of the highest carrier mobility has led to highly anisotropic electrical, optical, thermal, and mechanical properties.…”
Section: Introductionsupporting
confidence: 61%
“…Usually with application of strain, the deep conduction band states near Fermi comparatively shifts to lower energy than the lowest conduction band states; this causes change in the nature of band gap between direct or indirect. 23 In some cases similar to the present case, the variation in the valence band is also authoritatively significant to decide the nature of the band gap. On the structural front, a large anisotropy of black phosphorous along with one of the highest carrier mobility has led to highly anisotropic electrical, optical, thermal, and mechanical properties.…”
Section: Introductionsupporting
confidence: 61%
“…It should be noted that the available range of the compressive or tensile strain is determined by both the method to generate strains and the condition of the mechanical failure of strained materials. 52 Common strain-generating methods include lattice mismatch on the substrate, and thermal expansion or mechanical loading, which generally generate strains ranging from À12% to 25%. 53 Further stretching or compression should involve an investigation on the stability of strained materials.…”
Section: Strain-engineering Transport Properties Of Penta-sicmentioning
confidence: 99%
“…The unique geometry and novel properties of PG have stimulated a lot of study in the field of 2D materials, leading to the discovery of a new class of 2D materials entirely composed of pentagonal structural units explored theoretically [11][12][13][14][15][16][17][18][19][20][21][22][23][24] and experimentally. 25,26 On the other hand, it has been demonstrated that 2D materials can be used to construct van der Waals (vdW) heterostructures for electronic devices.…”
Section: Introductionmentioning
confidence: 99%